Prevalence of multidrug-resistant enterococci in a tertiary care hospital in Mumbai, India. - Vaibhav R Deshpande; Mohan G Karmarkar; Preeti R Mehta (Journal of Infection in Developing Countries)
This item has no abstract available. Use the links below to access the full text.